Strategi Pengumpulan dan Analisis Data dalam Penelitian Kualitatif Pendidikan - Haki, Ubay; Prahastiwi, Eka Danik; Selatan, Universitas Tapanuli (LPPM Universitas Bina Bangsa, 2024)
Qualitative research is an in-depth, flexible, and interactive approach to understanding social phenomena. Grounded in constructivism, this approach recognizes the plural, interactive, and exchange dimensions of social experience interpreted by individuals. Qualitative research emphasizes understanding phenomena from the perspective of participants, using interactive and flexible strategies. The aim is to provide a holistic understanding of behavior, perception, motivation, and action, with the researcher as a key instrument in the natural object condition. The method is inductive, prioritizes the meaning transmitted by participants, and analyzes phenomena naturally. Types of qualitative research, such as naturalistic, phenomenological, ethnographic, case studies, and historical methods, provide flexibility in approaching a variety of research contexts. Through explanations of data collection and analysis, qualitative research offers creative and engaged strategies, such as observation, interviews, and case studies. Overall, qualitative research is a relevant choice to answer complex research questions, especially those involving qualitative dimensions. In the world of scientific research, qualitative research stands out as a valuable tool in understanding the complexity and diversity of social phenomena